2021
DOI: 10.17576/geo-2021-1702-20
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh kawalan kendiri, pencarian sensasi dan pengherotan kognitif terhadap sikap pro-jenayah dalam kalangan belia institusi pengajian tinggi di Malaysia

Abstract: Banyak kajian lepas di Barat membuktikan faktor psikologikal menjadi asas kepada pembentukan sikap pro-jenayah dalam kalangan individu. Walau bagaimanapun, kajian yang mengaitkan faktor psikologikal dan sikap pro-jenayah masih terhad dalam konteks Malaysia. Justeru, kajian ini bertujuan mengenal pasti hubungan serta pengaruh tiga faktor psikologikal iaitu kawalan kendiri, pencarian sensasi dan pengherotan kognitif terhadap sikap pro-jenayah dalam kalangan belia di Malaysia. Kajian menggunakan reka bentuk kuant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Other researchers such as Azizi et.al (2012); Thompson et.al (2017); Hamidah (2013) also agreed that such relationships exist as the parenting styles influence the development of the behaviors of their childrenAs with self-control, its relationship to students' misbehaviors is also weak. According to Yen et al (2021) self-control effects students' misbehaviors. But in this study it was found that the influence of peers shows significant relationships with students' misbehaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers such as Azizi et.al (2012); Thompson et.al (2017); Hamidah (2013) also agreed that such relationships exist as the parenting styles influence the development of the behaviors of their childrenAs with self-control, its relationship to students' misbehaviors is also weak. According to Yen et al (2021) self-control effects students' misbehaviors. But in this study it was found that the influence of peers shows significant relationships with students' misbehaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Some Theories agree that self-control (self-regulation, effortful control, self-discipline) taps into a common ability to direct their cognition, emotions, impulses, performances, and behaviors (Bridgett et al, 2015;Nigg, 2017). In fact, Yen et al (2021) found that three psychological factors (self-control, sensation seeking and cognitive distortion) were significantly associated with pro-criminal attitudes. A Research finding from a study by Adlya et al (2020) significant contribution of self-control to students' discipline that shows the r score value of 0.590 which means that there is a strong relationship between self-control and students' discipline.…”
Section: Self-control and Misbehaviorsmentioning
confidence: 99%